2011
DOI: 10.1007/s10593-011-0653-z
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of the behavior of succinyl dichloride in Friedel-Crafts reaction with thiophenes*

Abstract: Keywords: 4,4-di(2-thienyl)but-3-enoic acids, 4,4-di(2-thienyl)butyrolactones, 4-oxo-4-(2-thienyl)butyric acids, succinyl dichloride, 1,4-(2-thienyl)butane-1,4-diones, thiophenes, acylation.1,4-Di(2-thienyl)butane-1,4-diones are convenient starting materials for the preparation of 2,5-di(2-thienyl)pyrroles, -furans, and -thiophenes which, in turn, can serve as precursors of polymers and monomers which show electrical conductivity and particular photochemical properties [1]. The known syntheses of 1,4-dihetaryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Although several catalysts are now available as mentioned above, there have been sustained efforts towards the finding of new catalysts. Recently, Simirnov et al reported the preparation of 1,4-bis(2thienyl)butane-1,4-dione with SnCl4, TiCl4 and AlCl3 catalysts 8 . Although alkyl Lewis acids are weaker than common Lewis acids (AlCl3, FeCl3, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Although several catalysts are now available as mentioned above, there have been sustained efforts towards the finding of new catalysts. Recently, Simirnov et al reported the preparation of 1,4-bis(2thienyl)butane-1,4-dione with SnCl4, TiCl4 and AlCl3 catalysts 8 . Although alkyl Lewis acids are weaker than common Lewis acids (AlCl3, FeCl3, etc.…”
Section: Introductionmentioning
confidence: 99%